Penggunaan media sosial dalam meningkatkan literasi kesehatan di “Ayah ASI Indonesia” - Andy Mananohas; Tine Silvana Rachmawati; Rully Khairul Anwar (Jurnal Informatio, 2023)
The lack of information about breast milk is caused by the social media that tend to focus the information toward mothers, not to fathers or husbands. “Ayah ASI Indonesia” is a health information center on breast milk and breast-feeding that aims to fathers which uses social media to distribute the information. This study aims to identify and to comprehend the use of social media in increasing health literacy of husbands by Ayah ASI. The research method used is qualitative with a case study approach. Data collection techniques used are observation, interviews, and literature study. Meanwhile, the data analysis technique includes data reduction, data presentation, and creating conclusions. The informants of this study consisted of several founders and members of Ayah ASI Indonesia. The results of this research show that Ayah ASI Indonesia uses various existing social media. In terms of increasing health literacy, Ayah ASI Indonesia has able able to assess collected information and then distributed them to its target as a form of developing health information. It is concluded that Ayah ASI Indonesia, by using social media has succeded to ask the fathers of husbands to actively support their wives. It is suggested that Ayah ASI Indonesia to continue providing health information in improving health literacy to fathers, especially prospective fathers who need health information to support breastfeeding mothers.